2021
DOI: 10.7759/cureus.19801
|View full text |Cite
|
Sign up to set email alerts
|

Determinants for Acceptance of COVID-19 Vaccine in Nigeria

Abstract: Background: The coronavirus disease 2019 (COVID-19) pandemic heralded an unprecedented race to the development of several vaccine candidates at record speeds never seen in global health. Within nine months, Pfizer-BioNTech’s COVID-19 vaccine was approved by the United States FDA. Unfortunately, while these advances were ongoing, there was a burgeoning epidemic of disinformation about the virus and the vaccines that affected the willingness of people, especially minority groups, to get vaccinated. In Nigeria, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 17 publications
4
26
0
7
Order By: Relevance
“…The Ipsos [ 49 ] study (country = 15, participants = 5932) conducted in partnership with the World Economic Forum found that perceptions of risk to health (side effects and speed of vaccine to market) perfectly described the reason for unwillingness to vaccinate against COVID-19. A similar pattern was reported in Ghana [ 50 ] and Nigeria [ 51 ]. Furthermore, in a survey of 5416 Africans, 37% of participants were hesitant to accept the COVID-19 immunization once available to them (with the highest level of hesitancy observed among participants from Central Africa; 67%), and 79% were concerned about its negative effects [ 52 ].…”
Section: Discussionsupporting
confidence: 88%
“…The Ipsos [ 49 ] study (country = 15, participants = 5932) conducted in partnership with the World Economic Forum found that perceptions of risk to health (side effects and speed of vaccine to market) perfectly described the reason for unwillingness to vaccinate against COVID-19. A similar pattern was reported in Ghana [ 50 ] and Nigeria [ 51 ]. Furthermore, in a survey of 5416 Africans, 37% of participants were hesitant to accept the COVID-19 immunization once available to them (with the highest level of hesitancy observed among participants from Central Africa; 67%), and 79% were concerned about its negative effects [ 52 ].…”
Section: Discussionsupporting
confidence: 88%
“…Surprisingly, celebrities' and leaders' advocacy on the COVID-19 vaccine would have no effect on respondents' decision to be vaccinated (69.3%) [18]. While most respondents (over 60%) in another study were willing to be vaccinated if recommended by their healthcare provider or health agencies [40]. The evading risk associated with COVID-19 severity was the most prevalent motivator [18].…”
Section: Motivators For Vaccinationmentioning
confidence: 92%
“…Among healthcare staff and students in South Africa [40,41], most respondents are confident of vaccine effectiveness (97.4%), compatible with their religious beliefs (96.1%), important and safe (95.4%), and are willing to accept the vaccine (89.5%). In contrast, most respondents (74%) among 200 cancer patients surveyed had concerns about vaccine safety and effectiveness and the ability of the health authorities to vaccinate the Tunisian population [42].…”
Section: Motivators For Vaccinationmentioning
confidence: 99%
“…There have been several studies [13][14][15][16][17][18][19] on COVID-19 vaccine development, distribution, accessibility and impact. Studies [20][21][22][23][24][25][26][27] on public responses regarding acceptance of vaccines are likewise increasing in number, providing global, continental and national coverage. However, there is a lack of research on the acceptance of COVID-19 vaccines in Nigeria within its regional context.…”
Section: Methodsmentioning
confidence: 99%